2015
DOI: 10.5812/cardiovascmed.28086v2
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding heparinization of arterial line and maintaining acceptable arterial waveform after cardiac surgery: A randomized clinical trial

Abstract: Background:Invasive and continuous blood pressure (BP) monitoring is crucial after cardiac surgery. Accuracy of BP measurement mostly depends on patency of arterial catheter and acceptable waveform. Heparinized saline flush usually used for this purpose may be accompanied by potential heparin adverse effects.Objectives:The aim of this study was to compare heparinized and non-heparinized saline flush to maintain acceptable arterial waveform after cardiac surgery.Materials and Methods:In a double blind randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Routine arterial cannula maintenance includes regular flushing with heparin solution (HS, heparin plus 0.9% sodium chloride) to prevent cannula occlusion [4]. Other cannula maintenance procedures include the use of infusions under positive pressure to prevent retrograde blood flow [46]. Heparin is a powerful drug in terms of its ability to prevent clots from forming in the cannula, but its use is not without risk of bleeding, allergic reactions and low platelet counts [7].…”
Section: Introductionmentioning
confidence: 99%
“…Routine arterial cannula maintenance includes regular flushing with heparin solution (HS, heparin plus 0.9% sodium chloride) to prevent cannula occlusion [4]. Other cannula maintenance procedures include the use of infusions under positive pressure to prevent retrograde blood flow [46]. Heparin is a powerful drug in terms of its ability to prevent clots from forming in the cannula, but its use is not without risk of bleeding, allergic reactions and low platelet counts [7].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, once the time frame exceeds 48 h of arterial catheter placement, HS has a significant advantage with longer arterial catheter patency compared to SS ( 23 ). Alizadehasl showed that SS was as effective as HS at maintaining arterial catheter patency for 72–96 h ( 3 ). Moreover, it is not just arterial catheter patency that has been examined, a systematic review and meta-analysis reported that HS is slightly better than SS at maintaining the central venous catheter patency within a short-term period (<30 days), whereas there was not a significant difference between HS and SS in catheter patency in a long-term period (> 30 days) ( 24 ), although the intended use, the duration of catheter placement, and management method between the arterial catheter and the central venous catheter are different.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there have been no reports of complications in dogs given a continuous HS infusion during direct arterial blood pressure measurements at this stage, but the use of heparin in dogs is not risk free. Furthermore, in humans, it has been reported that SS provides acceptable direct arterial pressure waveform and is a cost-effective practice in the Intensive Care Unit (2,3,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…However,heparin increases clotting times and may result in fatal hemorrhages when doses are too high [50]. Frequent heparin flushing also affects the result of coagulation tests and disturbs the monitoring of heparin dosage [51]. Therefore, this consensus recommends avoiding heparin flush during vascular access placement for severe COVID-19 patients with coagulation dysfunction.…”
Section: Preventionmentioning
confidence: 99%